Nanoscale extracellular vesicle-derived DNA is superior to circulating cell-free DNA for mutation detection in early-stage non-small-cell lung cancer. (18th October 2018) - Wan, Y; Liu, B; Lei, H; Zhang, B; Wang, Y; Huang, H; Chen, S; Feng, Y; Zhu, L; Gu, Y; Zhang, Q; Ma, H; et al.
Abstract: Background: The comparison between relatively intact nanoscale extracellular vesicle-derived DNA (nEV-DNA) and fragmented circulating cell-free DNA (cfDNA) in mutation detection among patients with non-small-cell lung cancer (NSCLC) has not been carried out yet, and thus deserves investigation. Patients and methods: Both nEV-DNA and cfDNA was obtained from 377 NSCLC patients with known EGFR mutation status and 69 controls. The respective EGFR E19del/T790M/L858R mutation status was interrogated with amplification-refractory-mutation-system-based PCR assays (ARMS-PCR). Results: Neither nEV-DNA nor cfDNA levels show a strong correlation with tumor volumes. There is no correlation between cfDNA and nEV-DNA levels either. The detection sensitivity of nEV-DNA and cfDNA using ARMS-PCR in early-stage NSCLC was 25.7% and 14.2%, respectively, with 96.6% and 91.7% specificity, respectively. In late-stage NSCLC, both nEV-DNA and cfDNA show ∼80% sensitivity and over 95% specificity. Conclusions: nEV-DNA is superior to cfDNA for mutation detection in early-stage NSCLC using ARMS-PCR. However, the advantages vanish in late-stage NSCLC.